A collaborative learning approach to improving health worker performance in adolescent sexual and reproductive health service provision: a descriptive feasibility study in six health zones in the Democratic Republic of the Congo - Sylvie Olela Odimba; Frances Squires; Erin Ferenchick; Symplice Mbola Mbassi; Paul Chick; Marina Plesons; Venkatraman Chandra-Mouli (Global Health Action)
Poor performance among health service providers is a key barrier to high quality, adolescent-responsive health services. Collaborative learning has been shown to strengthen health service provider performance, but few studies have examined its implementation in adolescent health services. In this paper, we describe a collaborative learning approach for adolescent health service providers implemented as part of a project aiming to prevent HIV in adolescent girls and young women in the Democratic Republic of the Congo (DRC) and explore its feasibility, acceptability, benefits and challenges. To do so, we reviewed plans, budgets and progress reports, as well as nested implementation research related to the project. We also carried out a quantitative analysis of the number, location, participants and topics of collaborative learning sessions conducted as part of this initiative, and thematic analysis to synthesise findings on perceived benefits and challenges. Under the project, 32 collaborative learning sessions of approximately two-hour duration were held with up to 15 participants, most of whom were nurses, between June 2018 and May 2019. The project cost was approximately USD 135,000 over three years. Reported benefits included improving health service provider attitudes, knowledge and skills; ensuring delivery of non-judgemental, empathic and confidential health services; and improving communication and collaboration between health services and adolescents together with their parents. While the novelty of the approach in this context presented challenges, our results suggest that collaborative learning in adolescent health services is feasible, acceptable, and inexpensive. It may help strengthen the knowledge and skills of health service providers, build positive attitudes and motivation, and improve their performance and thereby the adolescent-responsiveness of health services. Further research is needed to confirm these results in other settings and to examine the impact of collaborative learning on the acceptability and uptake of health services.